2018
DOI: 10.3389/fmicb.2018.00249
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Response of Staphylococcus aureus to Sunlight in Oxic and Anoxic Conditions

Abstract: The transcriptional response of Staphylococcus aureus strain Newman to sunlight exposure was investigated under both oxic and anoxic conditions using RNA sequencing to gain insight into potential mechanisms of inactivation. S. aureus is a pathogenic bacterium detected at recreational beaches which can cause gastrointestinal illness and skin infections, and is of increasing public health concern. To investigate the S. aureus photostress response in oligotrophic seawater, S. aureus cultures were suspended in sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…Porphyrins are a group of metabolites that have previously been linked to inflammation in acne via production of reactive oxygen species [36]. Several microbial species have been found to increase the secretion of porphyrins and upregulate enzymes responsible for porphyrin metabolism when exposed to hemin, an iron containing porphyrin found in hemoglobin [37, 38]. Consistent with these reports, we found that porphyrin metabolism was predicted to be upregulated in our aortitis group.…”
Section: Discussionsupporting
confidence: 89%
“…Porphyrins are a group of metabolites that have previously been linked to inflammation in acne via production of reactive oxygen species [36]. Several microbial species have been found to increase the secretion of porphyrins and upregulate enzymes responsible for porphyrin metabolism when exposed to hemin, an iron containing porphyrin found in hemoglobin [37, 38]. Consistent with these reports, we found that porphyrin metabolism was predicted to be upregulated in our aortitis group.…”
Section: Discussionsupporting
confidence: 89%
“…This phototoxicity, which is considered as a major contributor of bacterial die-off in the marine ecosystem (Lozano et al, 2020;Zaafrane & Maatouk, 2012), is the result of reactive oxygen species (ROS) such as superoxide, hydrogen peroxide, and hydroxyl radical generated by a natural or an artificial photosynthesizers when they are exposed to sunlight radiations (Imlay, 2019;Zinser, 2018). The ROS action has been recognized as an important factor causing DNA, protein, and lipid alteration and ultimately causes bacteria death (Ezraty et al, 2017;Hong et al, 2019;Matallana-Surget & Wattiez, 2013;McClary & Boehm, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For these three representative vital pathogenic bacteria of nosocomial infection, many studies have revealed the inactivation effect of visible light. For example, McClary and Boehm irradiated S. aureus with full spectrum light 6 hours and measured transcript abundance by RNA sequencing to find out that S. aureus was inhibited by full spectrum sunlight [ 20 ]. Exposing S. aureus , P. aeruginosa , and E. coli strains to a single blue laser irradiation (450 nm) and counting the number of living bacteria, De Sousa et al concluded that blue light significantly inhibited the growth of bacteria under low-intensity conditions [ 21 ].…”
Section: Introductionmentioning
confidence: 99%